Frontispiece: Mixed Group 14–15 Metalates as Model Compounds for Doped Lead Halide Perovskites. Issue 8 (12th February 2021) - Dehnhardt, Natalie; Luy, Jan‐Niclas; Klement, Philip; Schipplick, Luca; Chatterjee, Sangam; Tonner, Ralf; Heine, Johanna
Abstract : Perovskites In their Communication on page 3906, Ralf Tonner, Johanna Heine et al. present model compounds featuring [PbE2 I16 ] 8− (E=Sb, Bi) anions that represent precise cut‐outs of doped perovskites. The compounds display surprisingly low band gaps.